Hyperemesis gravidarum and eating disorders before and after pregnancy: A register-based study - Terävä-Utti, Eeva (Wiley, 2025)
Objective: Hyperemesis gravidarum (HG) is a severe form of excessive vomiting during pregnancy. The connection between psychiatric morbidity and HG has been debated, but only a few studies have focused on eating disorders (EDs). The objective of this study was to evaluate the association between HG and both pre-pregnancy and new post-pregnancy EDs.
Methods: A register-based controlled study. HG diagnoses were retrieved from healthcare registers between 2005 and 2017. Women with HG in their first pregnancy resulting in delivery were chosen as cases (n = 4265; the HG group) and women with no HG as controls (n = 302,663; the non-HG group). The associations between EDs and HG were analyzed by binary logistic regression, adjusted with age, body mass index, smoking, socioeconomic status, and pre-pregnancy psychiatric diagnoses.
Results: In the HG group, 1.6% and in the non-HG group, 0.2% had a pre-pregnancy ED. Women with ED were more likely to have HG in their first pregnancy compared with women with no history of EDs (adjusted odds ratio [AOR] 9.4, 95% CI 6.52-13.66, p < .0001). Moreover, 0.4% of the women in the HG group and 0.1% of the women in the non-HG group had a new ED diagnosis after pregnancy, and thus the women in the HG group were more likely to have an ED diagnosis after pregnancy (AOR I 3.5, 95% CI 1.71-7.15, p < .001, AOR II 2.7, 95% CI 1.30-5.69, p = .008).
Discussion: We found a bidirectional association between ED and HG, suggesting a shared etiology or risk factors between these disorders. This finding emphasizes the importance of collaboration across various specialties when treating these patients.
Public significance: Our findings suggest a bidirectional association between HG and EDs before and after pregnancy. This finding provides essential information for healthcare professionals working with pregnant women. As both of these disorders are known to have far-reaching effects on the lives of both the mother and her offspring, our results help clinicians to target special attention and interventions to the patients suffering from these disorders.